Circular photocurrents in centrosymmetric semiconductors with hidden spin polarization - Kexin Wang; Butian Zhang; Chengyu Yan; Luojun Du; Shun Wang (Nature Communications)
Abstract Centrosymmetric materials with site inversion asymmetries possess hidden spin polarization, which remains challenging to be converted into spin currents because the global inversion symmetry is still conserved. This study demonstrates the spin-polarized circular photocurrents in centrosymmetric transition metal dichalcogenide semiconductors at normal incidence without applying electric bias. The global inversion symmetry is broken by using a spatially-varying circularly polarized light beam, which could generate spin gradient owing to the hidden spin polarization. The dependence of the circular photocurrents on electrode configuration, illumination position, and beam spot size indicates an emergence of circulating electric current under spatially inhomogeneous light, which is associated with the deflection of spin-polarized current through the inverse spin Hall effect. The circular photocurrents is subsequently utilized to probe the spin polarization and the inverse spin Hall effect under different excitation wavelengths and temperatures. The results of this study demonstrate the feasibility of using centrosymmetric materials with hidden spin polarization and non-vanishing Berry curvature for spintronic device applications.